Pendidikan Literasi Keuangan bagi Santri-Santriwati Usia Remaja - Faerrosa, Lady; Dewi, Puspita; Ibrahim, Isra Dewi Kuntary; Pratama, Aryan Agus (LPPM Universitas Bumigora, 2024)
Financial literacy is widely believed to be very important. The aim of this community service activity was carried out to reflect the team's awareness that youth financial literacy in Lombok is still very limited, especially in relatively small boarding schools. As it is known that most of the students at the Nurul Jannah Orphanage do not have complete parents to provide basic education regarding financial literacy, the orphanage is seen as the right location to be given insight and knowledge related to financial management. The method for implementing financial literacy education in this community service is through project based learning. This community service began with thorough need analysis, material delivery, and project-based learning attended by 50 students. The results of this community service activity shows that the students are able to implement the material presented in financial management based on wise budgeting between needs, wants, savings, and investments. Not only that, participants were also able to design a simple business according to the capital given by the team.